THE PROPAGATION OF ORCHID THROUGH FORMATION OF PROTOCORM LIKE BODIES (PLB) FOR SUPPORTING THE RESQUE OF Phalaenopsis ORCHID IN INDONESIA - Budi Kriswanto; Sigit Soeparjono; Didik Pudji Restanto (UNEJ e-Proceeding, 2017)
Indonesia is a tropical country that has large orchid germ plasm because it has tropicalforests along the equatorial regions (islands of Sumatra, Kalimantan, Sulawesi and Papua) Recently, there has been changed become oil palm plantations and climate change, which hascaused the extinction of orchid. The Phalaenopsis orchid is an orchid that has high exotic andcommercial value. The purpose of this study was to maintain the Phalaenopsis throughpropagation of Protocorm Like Bodies (PLB). This study used the treatment of different kindsof basal medium Murashige & Skoog (MS), ½ Murashige & Skoog (1/2 MS) and Vacin& Went(VW) and 6-benzylaminopurine (BAP) and α-naphthylacetic acid (NAA) concentrations ongrowth and propagation of PLB. The results showed sequentially VW, ½ MS and MS mediaprovided the best plb growth and media ½ MS provides regeneration plb into a good planletin which shoots and roots formed. Treatment of plant growth regulator of BAP: NAA effect ondiameter of plb colony and individual size of plb with 2.1 cm and 0.2 cm, respectively.